Determinants of job satisfaction among employee in Tabung Haji Negeri Sembilan / Azura Azrin Azman - Azman, Azura Azrin (Faculty of Business and Management, 2019)
Employee job satisfaction is one of the key goals of HR personnel. Therefore, it is important for the organization to increase the level of employee job satisfaction to achieve organization’s goals and increase productivity. Lack of satisfaction may lead to low performance and decline the productivity of the organization. Malaysia is one of the country that have the best level of job satisfaction compared to other country. Thus, this study attempts to examine the determinants of employee job satisfaction in banking industry in government link company (GLC). This research is a quantitative research which had used past researcher questionnaire as the instrument for the collection of data. The study was conducted in all branches of Tabung Haji Negeri Sembilan which is 10 branches with a sample of 106 respondent. Sampling method used in this study is convenience sampling. The four dimensions of relationship in employee job satisfaction are considered in this study which salary, supervision, promotion and co-worker support. The data was analysed using Statistical Package for the Social Science (SPSS) software in order to find out correlation coefficient and regression. From the result of this study, it indicates that only from the variable salary, supervision, promotion and co-worker support only salary and co-worker support that may influence employee job satisfaction in Tabung Haji Negeri Sembilan. From the hypothesis, only two hypothesis were accepted and other two is rejected. The most significant factor that influence employee job satisfaction is co-worker support with significant value at 0.000 .